Pengaruh Model Pembelajaran Probing Prompting Terhadap Hasil Belajar Siswa di SMPN 2 Tanjungpinang - MILASARI MILA (GHIROH, 2025)
This study aims to determine whether there is an effect of applying the probing prompting learning model on the learning outcomes of eighth-grade students in Islamic Religious Education at SMPN 2 Tanjungpinang. Based on observations, teachers' questions can also stimulate children to improve their learning outcomes, so creativity and diversity in question models are needed to strengthen students' comprehension skills. Meanwhile, based on the questionnaire, it was found that there is an effect on students' learning outcomes with the application of the probing-prompting learning model in the subject of Islamic Religious Education. The calculated value of rxy = 0.434 falls between the values (0.40-0.60). Thus, rxy = 0.434 is greater than the r table at the 5% significance level and the 1% significance level (0.2586 < 0.3357 < 0.434), meaning that Ha is accepted and Ho is rejected. Therefore, it can be concluded that there is a significant relationship between the application of the probing-promoting learning model for eighth-grade students and their learning outcomes at SMPN 2 Tanjungpinang.